Bifurcation of Archetypes in Mykhailo Kotsiubynskyi’s Novel “Shadows of Forgotten Ancestors” - Dzera, Oksana; Molchko, Oksana (Vertimo studijos, 2024)
This article reinterprets Mykhailo Kotsiubynskyi’s “Shadows of Forgotten Ancestors” by moving beyond the traditional view of the novel as a Hutsul “Romeo and Juliet” tale centered on a family feud. Applying Carl Jung’s theory of archetypes, the study explores how the narrative unfolds deeper psychological themes, including the Shadow, the Anima, the Wise Old Man, and the Changeling. The analysis reveals that the true essence of the novel lies in the protagonist’s struggle with his darker nature, his unfulfilled redemption, and the symbolic duality of the feminine, offering a universal exploration of identity, duality, and the human psyche. The authors integrate the overlapping of paganism and Christianity in the novel with the theory of archetypes, emphasizing how these elements shape the protagonist’s character and fate.
Keywords: archetypes; collective unconscious; bifurcation; Shadow; Anima; Changeling